Use of Phosphate Binders in End-Stage Renal Disease: An Experience From a Secondary Care Hospital in United Arab Emirates - Rabbani, Syed Arman (J Pharm Bioallied Sci, 2019)
OBJECTIVE: Hyperphosphatemia in end-stage renal disease (ESRD) is associated with many serious patient-level consequences including cardiovascular events and mortality. The purpose of this study was to investigate the use of phosphate binders in ESRD patients on maintenance hemodialysis. MATERIALS AND METHODS: The study was a prospective observational cohort study including adult ESRD patients undergoing hemodialysis at a secondary hospital in United Arab Emirates. Patient characteristics were compared as per type of phosphate binder used. Bivariate and multivariate multinomial logistic regression analyses were carried out to determine variables that were independently associated with use of different phosphate binders. RESULTS: Phosphate binders used at our study site were sevelamer, calcium carbonate, and a combination of sevelamer and calcium carbonate. Bivariate multinomial logistic regression analysis revealed that serum phosphorous (odds ratio [OR]: 0.14, 95% confidence interval [CI]: 0.04–1.09, P = 0.047; OR: 0.10, 95% CI: 0.03–0.89, P = 0.042), calcium (OR: 0.11, 95% CI: 0.02–0.86, P = 0.041; OR: 0.22, 95% CI: 0.01–0.96, P = 0.012), and calcium–phosphorous product (OR: 0.20, 95% CI: 0.06–0.64, P = 0.008; OR: 0.16, 95% CI: 0.05–0.54, P = 0.003) levels were significantly lower in patients on sevelamer per se as well as in patients on combination therapy, respectively when compared to calcium carbonate per se. Multivariate multinomial logistic regression analysis revealed that in sevelamer and combination groups, cardiovascular diseases (OR: 0.12, 95% CI: 0.02–0.65, P = 0.022; OR: 0.10, 95% CI: 0.01–0.88, P = 0.038) were significantly lesser compared to calcium carbonate group after being adjusted for other variables in the model. CONCLUSION: We observed that hyperphosphatemia and related events in our study population were better controlled by sevelamer per se and combination therapy than calcium carbonate per se. Further large scale, multicenter studies are required to confirm and establish these findings.